Wenn man #f (x) = 2x ^ 2 + 3 # und g (x) = 5x + 2 gibt, wie findet man # (3f (2) - 2g (2)) / (f (1) + g (1) ) #?

Antworten:

#3/4#

Erläuterung:

#f (Farbe (rot) (1)) = 2 (Farbe (rot) (1)) ^ 2 + 3 = 2 + 3 = 5 #

#f (Farbe (rot) (2)) = 2 (Farbe (rot) (2)) ^ 2 + 3 = 8 + 3 = 11 #

#g (Farbe (Magenta) (1)) = 5 (Farbe (Magenta) (1)) + 2 = 5 + 2 = 7 #

#g (Farbe (Magenta) (2)) = 5 (Farbe (Magenta) (2)) + 2 = 10 + 2 = 12 #

# "Werte in Ausdruck einfügen" #

#rArr ((3xx11) - (2xx12)) / (5 + 7) #

#=(33-24)/12#

#=9/12#

#=3/4#